2020
DOI: 10.1213/ane.0000000000004734
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Cardiac Arrest During Adult Liver Transplantation: Incidence and Risk Factor Analysis From 7 Academic Centers in the United States

Abstract: Background: Intraoperative cardiac arrest (ICA) has a reported frequency of 1 in 10,000 anesthetics but has a much higher estimated incidence in orthotopic liver transplantation (OLT). Single-center studies of ICA in OLT are limited by small sample size that prohibits multivariable regression analysis of risks. METHODS: Utilizing data from 7 academic medical centers, we performed a retrospective, observational study of 5296 adult liver transplant recipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…25 Patients with HCM in our study also appeared to have higher rates of ICA and perioperative cardiopulmonary complications (Table 2) than all LT patients in a multicenter study. 26 Two patients in our study experienced ICA; one patient who died in the operating room, which was similar to the result reported by Smith et al 26 22 and are listed in the Box. Previously published data for patients not undergoing LT showed that TEE was rarely used for patients with HCM undergoing general surgery.…”
Section: Discussionsupporting
confidence: 89%
“…25 Patients with HCM in our study also appeared to have higher rates of ICA and perioperative cardiopulmonary complications (Table 2) than all LT patients in a multicenter study. 26 Two patients in our study experienced ICA; one patient who died in the operating room, which was similar to the result reported by Smith et al 26 22 and are listed in the Box. Previously published data for patients not undergoing LT showed that TEE was rarely used for patients with HCM undergoing general surgery.…”
Section: Discussionsupporting
confidence: 89%
“…Catastrophic cardiopulmonary collapse is a risk at any stage of transplantation. Intraoperative cardiac arrest (ICA) occurs less frequently in LDLT than in DDLT (1‐2.4% vs. 3‐3.6%) 76,77 . ICA most commonly occurs secondary to PRS, hyperkalemia, and bleeding at reperfusion.…”
Section: Essentials Of Anesthetic Management Of Ldlt Recipientsmentioning
confidence: 99%
“…However, ICA during dissection and the anhepatic phase may also occur due to hemorrhage, intracardiac thrombus (ICT), or pulmonary thromboembolism (PTE) 76,78 . In a large, multicenter, retrospective review, LDLT was a risk factor associated with ICA (OR 2.13; 95% CI [1.16‐3.89]; P = .014) 77 . Though the association between LDLT and ICA was based on small sample size (396 patients), outcomes from LDLT patients with ICA were promising, with a lower intraoperative mortality rate than DDLT patients (.5% vs. 1.1%) 77 …”
Section: Essentials Of Anesthetic Management Of Ldlt Recipientsmentioning
confidence: 99%
“…For the perioperative considerations, intraoperative cardiac arrest is a feared complication with reported rate of 3.7% and in almost 50% of the cases it is associated with the postreperfusion syndrome. 31 Dr Wagener, Columbia University, discussed the AHA guidelines to consider the early use of extracorporeal membrane oxygenation, which was demonstrated to have a higher probability of return to spontaneous circulation. 32 Dr Findlay, Mayo Clinic, presented new diagnostic criteria for cirrhotic cardiomyopathy in end-stage liver disease from the Cirrhotic Cardiomyopathy Consortium during the Liver Intensive Care Group of Europe symposium.…”
Section: Anesthesiology/critical Care/acute Liver Failurementioning
confidence: 99%